Radiological impact from 210Po in food marketed as “superfood” - F. Piñero-García; R. Thomas; E. Forssell-Aronsson; M. Isaksson (Applied Food Research)
The food industry marketing is promoting new nutrient sources marketed as “superfood” exploding in popularity due to their claimed benefits in boosting the health system. “Superfood” products gain popularity among consumers year by year, due to marketing and dietitian's recommendations. These food products can contain traces of radioactive elements such as 210Po, which has been identified as humans’ carcinogens. Therefore, the ingestion of 210Po, even at trace levels, could have an important radiological impact on human health. For that reason, the aim of the current study is to determine the radiological impact of 210Po in food marketed as “superfood”. 210Po was detected in all samples analysed. The range of activity concentration was 0.09–40 Bq·kg-1, with an average activity concentration of 4 ± 8 Bq·kg-1. The median levels of 210Po in groups investigated decreased as follows: Seaweed (3.0 Bq·kg-1) > Fungi (2.4 Bq·kg-1) > Algae (1.5 Bq·kg-1) > Botanical (0.7 Bq·kg-1) > Insect (0.09 Bq·kg-1). As a result, the radiation dose exposure for consumers could increase around 1 – 90 μSv/y, depending on superfood product. On average, the inclusion of those products in the Swedish diet could increase between 2 and 12 % the total dose received by 210Po and food consumption.